EFL Learners’ Big Five Personalities, Language Learning Strategies, and Speaking Skills - Marpaung, Dea Venda; Widyantoro, Agus (Indonesian Journal of EFL and Linguistics, 2020)
Accommodating learners’ individual differences including personalities and language learning strategies is important in implementing the learner-centred instruction. This current research investigated the correlation of EFL learners’ Big Five personalities, language learning strategies, and speaking skills. It tried to answer the questions if there is (a) any correlation between the EFL learners’ Big Five personalities and speaking skills, (b) any correlation between the EFL learners’ learning strategies and speaking skills, and (c) any correlation between the predictor variables (EFL learners’ Big Five personalities and language learning strategies) and the criterion variable (speaking skills). This present study involved 357 students from 3 senior high schools in Pontianak, West Kalimantan, academic year 2018/2019. The data were obtained through questionnaires and speaking test. The data were analysed using statistical analysis through correlational and regression tests to answer the research questions. The results revealed that there was no significant correlation found between the EFL learners’ Big Five personalities and speaking skills (Sig. (2tailed)=0.464>alpha level 0.05), between the learners’ language learning strategies and speaking skills (Sig. (2tailed)=0.575>alpha level 0.05), and between the predictor variables and criterion variables (Sig. (2tailed)=0.712>alpha level 0.05). These results showed that other variables outside personality and language learning strategy might correlate to the learners’ speaking skills